ATP measurement as an objective method to measure environmental contamination in 9 hospitals in the Dutch/Belgian border area - Andreas van Arkel; Ina Willemsen; Linda Kilsdonk-Bode; Sindy Vlamings-Wagenaars; Anne van Oudheusden; Pascal De Waegemaeker; Isabel Leroux-Roels; Martine Verelst; Evelien Maas; Anita van Oosten; Patricia Willemse; Esther van Asselen; et al. (Antimicrobial Resistance and Infection Control, 2020)
Abstract Background The objective of this study was to determine the level of environmental contamination in hospitals in the Dutch/Belgian border area, using ATP measurements. Design A cross-sectional observational survey. Methods Standardized ATP measurements were conducted in 9 hospitals on 32 hospital wards. Thirty pre-defined surfaces per hospital ward were measured with the 3 M Clean Trace NG luminometer. Results are displayed in relative light units (RLU). RLU > 1000 was considered as “not clean.” Differences in RLU values were compared between countries, hospitals, fomite groups and medical specialties. Results A total of 960 ATP measurements were performed, ranging from 60 up to 120 per hospital. The median RLU-value was 568 (range: 3–277,586) and 37.7% of the measurements were rated as not clean (RLU > 1000). There were significant differences between countries, hospitals and fomite groups. Conclusion ATP measurements can be used as a more objective approach to determine the level of environmental contamination in hospitals. Significant differences in ATP levels were found between hospitals and between countries. Also, substantial differences were found between different fomite groups. These findings offer potential targets for improvement of cleanliness in healthcare facilities.